2016
DOI: 10.18203/2349-3291.ijcp20163141
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum vitamin D with acute lower respiratory infection in Indian children under 5 years: a case control study

Abstract: Acute lower respiratory infection (ALRI), primarily pneumonia and bronchiolitis, is a substantial cause of morbidity and mortality in children younger than 5 years of age, particularly in developing countries. Worldwide, 20% mortality among children aged less than 5 years is attributed to respiratory tract infections (predominantly pneumonia associated). With neonatal pneumonia inclusive, 35-40% mortality among children aged less than 5 years account for 2.04 million deaths/year. Southeast Asia stands first in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Rationale for study exclusion included: studies including adults, study populations other than critically ill children or with acute conditions and studies of circulating vitamin D levels and deficiency in healthy children or in children with chronic conditions. Four studies46–49 were excluded due to insufficient data reporting (online supplementary table 6). We also excluded three studies50–52 that used the same cohort of children and included a single study to represent the cohort 53.…”
Section: Resultsmentioning
confidence: 99%
“…Rationale for study exclusion included: studies including adults, study populations other than critically ill children or with acute conditions and studies of circulating vitamin D levels and deficiency in healthy children or in children with chronic conditions. Four studies46–49 were excluded due to insufficient data reporting (online supplementary table 6). We also excluded three studies50–52 that used the same cohort of children and included a single study to represent the cohort 53.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a prospective study of 28 Japanese children hospitalized with a lower respiratory tract infection demonstrated a significant association between vitamin D deficiency with excess oxygen and ventilation with the ventilator (30). In addition, Garg et al (1) reported that subclinical vitamin D deficiency is an important risk factor for the acute lower respiratory tract infection in children under 5 years of age. However, Beigelman et al (29) concluded that vitamin D deficiency is uncommon in children hospitalized with bronchiolitis RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lower respiratory tract infection, primary pneumonia, and bronchiolitis are the most important causes of mortality and morbidity in children under 5 years of age in developing countries (1). In addition, bronchiolitis is the most common lower respiratory tract infection of viral origin in infants (2).…”
Section: Introductionmentioning
confidence: 99%
“…Rationale for study exclusion included: studies including adults, study populations other than critically ill children or with acute conditions, studies of circulating vitamin D levels and deficiency in healthy children or in children with chronic conditions. Four studies [40][41][42][43] were excluded due to insufficient data reporting (Additional Table 5). We also excluded three studies [44][45][46] that used the same cohort of children and included a single study to represent the cohort.…”
Section: Screening and Study Characteristicsmentioning
confidence: 99%